2006
DOI: 10.1136/jcp.2006.043539
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological risk factors for lymph node metastasis in submucosal invasive colorectal carcinoma of pedunculated or semipedunculated type

Abstract: Aims: To evaluate the histopathological risk factors for lymph node metastasis in cases of pedunculated or semipedunculated submucosal invasive colorectal carcinoma (SICC). Methods: A total of 48 patients with non-sessile SICC who underwent systematic lymph node dissection were included. Tumour size, histological grade, angiolymphatic invasion, tumour budding, dedifferentiation, objective submucosal invasion depth from the identified muscularis mucosa, relative invasion depth of the submucosal layer, and depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 25 publications
4
78
2
1
Order By: Relevance
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a strong association between budding and the presence of lymph node metastases and lymphovascular invasion, 11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] defined by the presence of tumor cells within an endothelium-lined space, and it has been suggested that buds represent the part of the tumor that has gained the ability to invade lymphatics and vascular channels. This idea is supported by two intriguing morphological studies: Morodomi et al 33 examined serial sections of high-budding areas to demonstrate that budding nests are often found adjacent to areas of lymphovascular space invasion, and, in a more recent study, Ohtsuki et al 31 performed double staining for anti-cytokeratin antibodies and anti-lymphatic antibodies, finding that a number of 'buds' at the invasive edge of a tumor are in fact located in small lymphatic spaces.…”
Section: Morphological Featuresmentioning
confidence: 99%
“…11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] On multivariate analysis, budding has consistently emerged as an independent adverse prognostic factor, associated with local tumor recurrence and distant metastases, and significantly worse overall and disease-free survival. 12,15,16,21,27,28,31,32,[34][35][36]38,40,41 The adverse prognostic impact of high-grade tumor budding is seen in both early and advanced colorectal carcinoma, and there are several scenarios in which this feature might influence clinical decision making, particularly in early colorectal carcinoma.…”
Section: Clinical Significance Of Tumor Buddingmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, measured submucosal invasion depths might be inconsistent. Although several authors measure the depth of submucosal invasion as the vertical distance from the surface of the lesion and the deepest portion of invasion [6], others consider as a baseline the line between the ends of the residual muscularis mucosae [61] in order to rule out the bias of the effect of the ischaemic erosion or biopsy distortion of the most superficial sectors of the lesion. Conclusive evidence is lacking and further work is needed in this area.…”
Section: Amentioning
confidence: 99%
“…A significant association between tumor budding and lymph node positivity has been consistently demonstrated correlating with tumor aggressiveness and more advanced TNM stage [32][33][34][35][36][37][38][39][40][41][42][43] . Tumor budding is frequently associated with poorly differentiated tumors, and with the presence of vascular and lymphatic invasion independently of disease extent [44][45][46][47][48] .…”
Section: Prognostic Impact Of Tumor Buddingmentioning
confidence: 99%